Peningkatan Prestasi Belajar Matematika Pada Materi Persamaan Garis Melalui Metode Think Pair Share Pada Siswa SMP - Sepni Yanti (Jurnal Ilmiah Wahana Pendidikan, 2020)
The research aims to find out the strategies and applications of character education at school which are balanced with Islamic religious learning at Attaqwa Bekasi West Java Middle School. This research method is a qualitative study whose data is obtained from observations, questionnaires, interviews, and documentation. The results of this study indicate that character education coupled with religious learning has a real character learning strategy, such as visiting an orphanage, doing real practices such as reading the Quran ( holy book ). Character education must be integrated in religious education. The role of religion can meet the needs humans in terms of the directors, mentors, and balancing characters of students.